The Urbanization of Indians in Winnipeg, Toronto, Edmonton and Vancouver: A Comparative Analysis - McCaskill, Don (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1981)
This study undertakes a comparative analysis of the migration, adjustment and integration of Indians into four large Canadian cities. The study explores several dimensions of the urbanization of Native people including: motivational determinants of the migration, employment and income structures, kinship networks, institutional participation, social adjustment, and return migration. The analysis demonstrates that Native people in urban areas exhibit low levels of economic adjustment and do not extend their participation into the institutions of the larger society. Rather, they appear to exhibit a “dual orientation” pattern of urban accommodation, exploiting the city for economic purposes but looking to the reserves for ideology, cultural identity, and social ties.